Polyethylene Blend
By preparing polyethylene mixtures of specific ingredients and process flows, the problems of benzene residue, insufficient mechanical properties, impure color and poor homogeneity in recycled polyethylene are solved, and a polyethylene mixture with high purity, high consistency and excellent mechanical properties can be achieved, which can directly replace virgin polyethylene for packaging and bottle manufacturing.
Patent Information
- Application Number
- JP2023572889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-31
- Filing Date
- 2022-05-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-05-31
AI Technical Summary
In the prior art, the polyethylene mixture used for extracting from recycled plastics has a problem of benzene residue, resulting in limited application in the fields of medical packaging, food packaging, etc. In addition, the mechanical properties of traditional recycled polyethylene are insufficient, requiring additional improved ingredients, impure color, and poor homogeneity, resulting in high OCS gel counts.
By preparing a polyethylene mixture, it has a specific melt flow rate, density and component distribution, including a C2 fraction above 95%, a specific content range of Homopolymer and Copolymer, and optional iso-PP fractions. The mixture ensures high purity and consistency through a strict process flow, from separation, washing, color-sorting to pelletization.
The high purity and consistency of polyethylene mixtures are achieved, and can directly replace virgin polyethylene for applications such as bottles and packaging. It has excellent mechanical properties and color purity, which reduces OCS gel counting and improves the controllability of the production process.
Smart Images

Figure 0007671871000001 
Figure 0007671871000002 
Figure 0007671871000003
Abstract
Description
[Technical field]
[0001] The present invention relates to polyethylene blends derived from recycled materials. [Background technology]
[0002] Many attempts have been made to purify recycle streams derived from post-consumer waste. Among those measures, washing, sieving, aeration, distillation, etc. may be mentioned. For example, WO2018046578 discloses a process for producing polyolefin recycle from mixed colored polyolefin waste, including packaging waste, comprising cold washing of the waste with water, followed by washing with an alkaline medium at 60°C, followed by flake color sorting to receive a color-sorted (white, clear, other color) monopolyolefin-rich fraction. These fractions are then treated at 50-155°C. Welle, F. (2005). Develop, a food grade HDPE recycling process. The waste & Resources Action Programme, Oxfordshire (Oxon) reports the recycling of milk bottles with the aim of preparing food grade HDPE. U.S. Pat. No. 5,767,230A describes a process that involves contacting a PCR polyolefin chip containing volatile impurities with a heated gas at a superficial velocity sufficient to substantially reduce the volatile impurities, such as odor-active substances. However, some problems remain. In the first aspect, benzene is frequently found in post-consumer recyclates, the origin of which remains unclear, but which impedes end-use applications in areas such as medical packaging, food packaging, etc. Residual amounts, i.e. trace amounts of benzene, are particularly problematic, as they make odor testing by sniffing experiments impossible, thus preventing end-uses with certain requirements regarding odor. In the second aspect, the mechanical properties of conventional post-consumer polyethylene, such as notched Charpy impact (at 23°C and -20°C), ESCR, FNCT and drop test stability, are quite poor, which necessitates expensive and per se undesirable upgrading components. In the third aspect, color remains yet another problem that has not been fully addressed. Many reuse applications require materials that are closer to what is usually described as white, or alternatively, what is usually described as transparent. As a further problem, known post-consumer recyclates suffer from a lack of homogeneity, as reflected by too high OCS gel count levels. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2018046578 Brochure [Patent Document 2] U.S. Patent No. 5,767,230A [Non-patent literature]
[0004] [Non-Patent Document 1] Welle, F. (2005). Develop, a food grade HDPE recycling process. The waste & Resources Action Programme, Oxfordshire Summary of the Invention [Problem to be solved by the invention]
[0005] Thus, the challenge remains to provide more valuable polyethylene blends. [Means for solving the problem]
[0006] The present invention provides a polyethylene blend comprising: (i) a melt flow rate (ISO 1133, 5.0 kg; 190° C.) of 0.1 to 10 g / 10 min, preferably 0.5 to 5.0 g / 10 min, more preferably 0.7 to 4.0 g / 10 min, and most preferably 1.0 to 3.0 g / 10 min; and (ii) 950-970 kg / m 3 density (ISO1183), and (iii) a C2 fraction in an amount of more than 95.0 wt.%, preferably more than 97.0 wt.%, as determined by NMR of the d2-tetrachloroethylene soluble fraction; and (iv) a homopolymer fraction (HPF) content, determined according to a chemical composition analysis by cross fractionation chromatography (CFC), in the range of 80.0 to 91.0 wt. %, and (v) a copolymer fraction (CPF) content, determined according to chemical composition analysis by cross fractionation chromatography (CFC), ranging from 9.0 to 20.0 wt. %, and (vi) optionally an iso-PP fraction (IPPF) content determined according to a chemical composition analysis by cross-fractionation chromatography (CFC) in the range of 0-2.0 wt.%, preferably 0-0.5 wt.%, where the iso-PP fraction (IPPF) is defined as the polymer fraction eluting at a temperature equal to or greater than 104° C., the homopolymer fraction (HPF), the copolymer fraction (CPF), and the iso-PP fraction (IPPF) together amount to 100 wt.%, and (vii) 0.01 to 2.00 wt. % inorganic residue (as measured by TGA) based on the total polyethylene blend; and (viii) A 10m OCS counting device with a count rate of 500-5,000 counts per square meter. 2 OCS gels with sizes between 100 and 299 micrometers measured on a film having (ix) The polyethylene blend comprises: 75.0~86.0L * , -5.0~0.0 a * , b between 5.0 and 25.0 * , measured according to DIN EN ISO11664-4 in the CIELAB color space (L * a * b * ) or or (x) The polyethylene blend comprises: -L over 86.0~97.0 * , -5.0~0.0 a * , b between 0.0 and 5.0 * , CIELAB color space (L * a * b * The present invention provides a polyethylene blend having a
[0007] The present invention also relates to a polyethylene blend in pellet form. The present invention further provides articles made therefrom, in particular bottles, and uses of the polyethylene blend for packaging. In a still further aspect, the present invention relates to a blend of the polyethylene blend with at least one virgin polyolefin and / or recycled polyolefin.
[0008] The term "polyethylene blend" is defined as the presence of at least two different polyethylenes, such as two high density polyethylenes that differ with respect to density. For example, a bimodal polyethylene obtained from two reactors operated under different conditions constitutes a polyethylene blend, in this case an in-situ blend of the two reactor products. Polyethylene blends obtained from consumer waste obviously contain a wide variety of polyethylenes. In addition to contamination with other plastics, mainly polypropylene, polystyrene, polyamides and polyesters, long-term degradation products of wood, paper, limonene, aldehydes, ketones, fatty acids, metals and / or stabilizers may also be found. It goes without saying that such contaminants are undesirable. It should be understood that the polyethylene blends of the present invention are not mass produced (impersonal) blends as some of the commercially available recyclables, but rather should be compared to virgin blends.
[0009] The term "C2 fraction" refers to a quantitative 13 It means repeating -[C2H4]- units derived from ethylene present in the linear backbone and short chain branches as determined by C{1H} NMR spectroscopy, where repeating means at least two units. The C2 fraction is wt C2画分 =fC C2全 ×100 / (fC C2全 +fC PP ) In the above formula, fC C2全 =(Iddg-ItwoB4)+(IstarB1×6)+(IstarB2×7)+(ItwoB4×9)+(IthreeB5×10)+((IstarB4plus-ItwoB4-IthreeB5)×7)+(I3s×3) and fC PP =Isαα×3 It is. Further details are given in the Experimental Section.
[0010] Since HDPE, LDPE or LLDPE, homopolymer and copolymer polyethylenes are present in the recycled blends, analytical separation becomes essential for characterization. A suitable method is chemical composition analysis by cross fractionation chromatography (CFC). This method has been described and successfully implemented by Polymer Char, Valencia Technology Park, Gustave Eiffel 8, Paterna E-46980 Valencia, Spain. Chemical composition analysis by cross fractionation chromatography (CFC) allows fractionation into homopolymer fraction (HPF) and copolymer fraction (CPF) as well as the iso-PP fraction potentially present (IPPF). The homopolymer fraction (HPF) is the fraction that contains polyethylene similar to homopolymer-HDPE. The copolymer fraction (CPF) is the fraction similar to polyethylene HDPE copolymers, but may also contain LDPE and LLDPE fractions. The iso-PP fraction (IPPF) is defined as the polymer fraction that contains isotactic polypropylene and elutes at temperatures above 104°C. The homopolymer fraction (HPF), copolymer fraction (CPF) and potentially iso-PP fraction (IPPF) add up to 100% by weight. It is self-evident that 100% by weight is given for material that is soluble within the cross fractionation chromatography (CFC) experiment. In addition to the chemical composition analysis by cross fractionation chromatography (CFC), the polyethylene blend according to the invention is also characterized by a C2 fraction in an amount of more than 95.0 wt.%, preferably more than 97.0 wt.%, as determined by NMR of the d2-tetrachloroethylene solubles. The percentages are given relative to the d2-tetrachloroethylene soluble portion used for the NMR experiments. The term "C2 fraction" is equivalent to the polymer fraction that can be obtained from ethylene monomer units, i.e. not from propylene monomer units. The upper limit of the "C2 fraction" is 100% by weight.
[0011] The present invention is based on the surprising discovery that the polyethylene blends described herein allow for direct replacement of virgin polyethylene.
[0012] The polyethylene blends according to the invention typically have a melt flow rate (ISO 1133, 5.0 kg; 190° C.) of 0.1 to 10 g / 10 min. The melt flow rate can be influenced, for example but not limited to, by extended producer responsibility schemes, for example from the German DSD, or by splitting post-consumer plastic waste streams, which have been sorted from municipal solid waste into multiple pre-sorted fractions and recombined therefrom in an appropriate manner. Usually the MFR is in the range of 0.5 to 5.0 g / 10 min, preferably 0.7 to 4.0 g / 10 min, most preferably 1.0 to 3.0 g / 10 min.
[0013] The polyethylene blend according to the present invention has a C2 fraction in an amount greater than 95.0 wt.%, preferably greater than 97.0 wt.%, more preferably greater than 98.0 wt.%, and most preferably greater than 99.0 wt.% of the d2-tetrachloroethylene solubles as measured by NMR.
[0014] Typically, the polyethylene blends according to the present invention are recycled materials.
[0015] Typically, the nature of recycling can be assessed by the presence of one or more of the following: (1) A content of inorganic residues greater than 0.01% by weight (measured by TGA) and 10 m by an OCS counting device (preferably OCS-FSA100, supplier OCS GmbH (Optical Control Systems)) in the range of 500-5000 counts / m2. 2 OCS gels with sizes between 100 and 299 micrometers measured on a film of Alternatively, or in combination, (2) Limonene at levels equal to or greater than 0.5 ppm, as determined using solid-phase microextraction (HS-SPME-GC-MS); Alternatively, or in combination, (3) Fatty acids consisting of the group selected from acetic acid, butanoic acid, pentanoic acid, and hexanoic acid, in a total amount equal to or greater than 10 ppm, as determined using solid phase microextraction (HS-SPME-GC-MS).
[0016] It is understood that options (2) and (3) are preferred. "Fatty acids selected from the group consisting of acetic acid, butanoic acid, pentanoic acid and hexanoic acid" means adding together the individual amounts of acetic acid, butanoic acid, pentanoic acid and hexanoic acid (as determined by HS-SPME-GC-MS in ppm).
[0017] The detection limit for limonene in solid phase microextraction (HS-SPME-GC-MS) is below 0.1 ppm, i.e., trace amounts of these substances readily reveal their recycled nature.
[0018] It goes without saying that the amounts of inorganic residues, gels, limonene and fatty acids should be as low as possible.
[0019] It is particularly preferred that limonene, determined using solid phase microextraction (HS-SPME-GC-MS), is present in an amount of 0.1-25 ppm, even more preferably 0.1-20 ppm, and / or the total amount of fatty acids from the group of acetic acid, butanoic acid, pentanoic acid and hexanoic acid, determined using solid phase microextraction (HS-SPME-GC-MS), is present in a total amount of at least 10-500 ppm, more preferably 10-300 ppm, most preferably 10-180 ppm.
[0020] Regarding the colour, two embodiments can be distinguished: essentially colourless blends and essentially white blends.
[0021] The first embodiment (essentially colorless) polyethylene blend comprises: 75.0~86.0L* , -5.0~0.0 a * , b between 5.0 and 25.0 * , measured according to DIN EN ISO11664-4 in the CIELAB color space (L * a * b * ).
[0022] The second embodiment (essentially white) polyethylene blend is -L over 86.0~97.0 * , -5.0~0.0 a * , b between 0.0 and 5.0 * , measured according to DIN EN ISO11664-4 in the CIELAB color space (L * a * b * ).
[0023] The polyethylene blends according to the invention are preferably characterized by an odor (VDA270-B3) of less than or equal to 2.5, preferably less than or equal to 2.0. It should be understood that many commercial recycle grades that do not report odor may in fact even be unacceptable in this respect, since the odor test indicated by VDA270 is prohibited due to the presence of problematic or toxic substances.
[0024] The polyethylene blend according to the present invention has the following properties (10 m 2 The gel count (measured on a film) of the OCS is one or more of the following characteristics: a) Size 300~599 micrometers: 100~2500 counts / square meter, b) Size 600~1000 micrometers: 5~200 counts / square meter, c) Size above 1000 micrometers: 1-40 counts / square meter. The OCS gel was measured at 10 2Given as counts per square meter calculated as an average for the film.
[0025] In yet a further embodiment, the polyethylene blend according to the invention has a tensile modulus (ISO 527-2 at a crosshead speed of 1 mm / min; 23° C.) using injection molded specimens (dogbone shape, 4 mm thickness) as described in EN ISO 1873-2 of at least 825 MPa, preferably at least 850 MPa, most preferably at least 910 MPa. Typically, the tensile modulus does not exceed 1100 MPa.
[0026] It is also preferred that the polyethylene blend, when subjected to NMR analysis as described herein, has no units derived from isotactic polypropylene.
[0027] In yet a further preferred embodiment, the polyethylene blend according to the invention has a LAOS-NLF1000% (190°C) of 2.1 to 2.9, preferably 2.2 to 2.7, most preferably 2.3 to 2.6. LAOS-NLF1000% is a rheological measure of the long chain branching content defined as follows:
number
[0028] A rather moderate or low value of LAOS-NLF 1000% indicates a rather low, i.e. practically negligible amount of LDPE or LLDPE. LAOS-NLF furthermore exhibits a non-linear polymer structure. Apart from sorting LDPE and LLDPE, it is possible to influence LAOS-NLF by mixing several recycle streams (after determination of the value) from different sources, for example from different conditions.
[0029] The polyethylene blend according to the present invention preferably has a shear thinning factor (STF) of more than 46.0, more preferably from 48.0 to 60.0.
number
[0030] In a further aspect, the polyethylene blend according to the present invention preferably has a polydispersity index (PI) of greater than 2.0, more preferably between 2.1 and 2.7.
number
[0031] The polyethylene blend according to the invention is preferably in the form of pellets, which contributes to a lower amount of volatile substances and also to homogenization.
[0032] The polyethylene blend of the present invention preferably has a Charpy notched impact strength of 35.0 kJ / m at 23°C. 2 Higher, more preferably 45 kJ / m at 23°C 2 At -20°C, the polyethylene blends according to the invention preferably have a Charpy notched impact strength of 18.0 kJ / m at 23°C. 2 Higher, preferably 22 kJ / m 2 Higher. The tensile yield stress is preferably greater than 25.0 MPa.
[0033] In a further aspect, the present invention relates to an article made from the polyethylene blends described herein. The polyethylene blends according to the present invention preferably comprise at least 95% by weight of the reactants to make the article. The article is preferably a bottle. In a preferred aspect, the polyethylene blends according to the present invention comprise an amount ranging from 95% to 98% by weight of the reactants to make the article. Preferably, the article is made only from the polyethylene blends according to the present invention and additives. In this embodiment, the additives are preferably selected from the group consisting of UV stabilizers, antioxidants and / or acid scavengers.
[0034] In yet a further aspect, the present invention relates to blends containing the polyethylene blends described herein and at least one virgin and / or recycled polyolefin. For example, virgin polyethylene homopolymer can be blended.
[0035] The present invention also relates to the polyethylene blends described herein for packaging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] The process for providing the polyethylene blend according to the present invention is very demanding. a) providing post-consumer plastic waste, preferably from a separate waste collection or municipal solid waste containing polyethylene; b) sorting objects made from polystyrene, polyamide, polypropylene, metal, paper and wood, thereby obtaining post-consumer plastic materials; c) sorting the colored material, thereby providing used plastic material including predominantly white bottles, predominantly white yogurt cups, predominantly white cans, predominantly colorless panels, predominantly colorless parts, etc.; d) optionally screening for impurities by manual inspection; e) receiving two streams of polyethylene material, a first stream being essentially clear and a second stream being essentially white; f) subjecting both streams separately to grinding and washing in aqueous solutions with various detergents followed by drying, windsifting and screening to obtain two pretreated streams; g) subjecting the two pretreated streams (both; separately) to further screening to remove non-polyolefin and colored fractions; h) extruding into pellets; i) an optional aeration step, which is preferably carried out by pre-heating the used plastic material to a temperature in the range of 100-130°C using an air flow having a temperature of at least 100°C, at such temperature for at least 7 hours or preferably for at least 20 hours; wherein steps b) and c) can be combined or carried out separately.
[0037] Venting is normally required, but may be omitted under certain circumstances. Odor control and assessment is possible by several methods. An overview is provided, inter alia, by Demets, Ruben et al., "Development and application of an analytical method to quantify odour removal in plastic waste recycling processes," Resources, Conservation and Recycling 161 (2020): 104907, which is incorporated herein by reference.
[0038] The present invention relates to a) providing post-consumer plastic waste, preferably from a separate waste collection or municipal solid waste containing polyethylene; b) sorting objects made from polystyrene, polyamide, polypropylene, metal, paper and wood, thereby obtaining post-consumer plastic materials; c) sorting the colored articles to provide a first intermediate stream of essentially colorless articles and a second intermediate stream of articles having an essentially white color; d) optionally screening for impurities by manual inspection; e) receiving two streams of polyethylene material, a first stream being essentially clear and a second stream being essentially white; f) subjecting both streams separately to grinding and washing in aqueous solutions with various detergents, followed by drying, winnowing and screening to obtain two pretreated streams; g) separately subjecting the two pretreated streams to further screening to remove non-polyolefin and color fractions; h) extruding into pellets; i) optionally aerating at a temperature in the range of 100-130°C; The present invention relates to a polyethylene blend as described herein which can be obtained from
[0039] Inorganic residues may be reduced by solution techniques, if necessary. OCS gel count parameters can be controlled to avoid contaminants such as pigments from colored materials, etc. Manual sorting is preferably assisted by NIR spectroscopy, which is also readily available in the form of small handheld devices. This allows the polypropylene content to be minimized. Density can be influenced by reducing the amount of relatively flexible polyethylene articles. The relative amounts of homopolymer fraction (HPF) and copolymer fraction (CPF) can be controlled by wind sorting (machines also called windsifters), using airflow the material is separated into various streams according to particle size, shape and especially weight. For example, polyethylene films (i.e. LLDPE / LDPE with a relatively high copolymer fraction (CPF)) can be rejected. CIELAB is controlled by a combination of color sorting and rejection of non-polyethylene polymeric impurities. EXAMPLES
[0040] experiment The following examples are included to demonstrate certain aspects and embodiments of the claimed invention. However, it should be understood by those of ordinary skill in the art that the following descriptions are illustrative only and should not be construed as limiting the invention in any way.
[0041] Test Method a) MFR The melt flow rate was measured at 190° C. under a load of 5.00 kg (MFR5). The melt flow rate is the amount of polymer in grams that an ISO 1133 standardized testing apparatus will extrude in 10 minutes at a temperature of 190° C. under a load of 5.00 kg.
[0042] b) Density Complies with ISO1183-1.
[0043] c) C2 fraction by NMR spectroscopy and overall microstructure including "continuous C3" and short chain branching quantitative 13 The C{1H} NMR spectrum is 1 H and 13 All spectra were recorded in solution using a Bruker AVNEO 400 MHz NMR spectrometer operating at 400.15 and 100.62 MHz for C, respectively. 13 A 10 mm extended temperature probe head optimized for C was used, and all air pressures were recorded using nitrogen gas. Approximately 200 mg of material was dissolved in about 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) with approximately 3 mg of BHT (2,6-di-tert-butyl-4-methylphenol, CAS128-37-0), and chromium(III) acetylacetonate (Cr(acac)3) {singh09}, giving a 60 mM solution of the relaxation agent in the solvent. To ensure a homogenous solution, the NMR tube was further heated in a rotating oven for at least 1 h after initial sample preparation in a heat block. After insertion into the magnet, the tube was spun at 10 Hz. Standard single-pulse excitation without NOE was employed, using an optimized tip angle, a recycle delay of 1 s, and a bilevel WALTZ16 decoupling scheme {zhou07, busico07}. A total of 6144 (6k) transients were acquired per spectrum. quantitative 13 C{1H} NMR spectra were processed and integrated using a proprietary computer program, and relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. Characteristic signals corresponding to polyethylene and polypropylene with different short chain branches (B1, B2, B4, B5, B6plus) were observed {randall89, brandolini00}.
[0044] Characteristic signals corresponding to the presence of polyethylene containing an isolated B1 branch (starB1 33.3 ppm), an isolated B2 branch (starB2 39.8 ppm), an isolated B4 branch (twoB4 23.4 ppm), an isolated B5 branch (threeB5 32.8 ppm), all branches longer than 4 carbons (starB4plus 38.3 ppm) and the third carbon from the saturated aliphatic chain end (3s 32.2 ppm) were observed. If one or the other structural element is not observable, it is excluded from the equation. The intensities of the combined ethylene backbone methine carbons (ddg) containing polyethylene backbone carbons (dd 30.0 ppm), γ-carbons (g 29.6 ppm), 4s carbons and threeB4 carbons (compensated later) are taken from 30.9 ppm to 29.3 ppm, excluding Tββ from polypropylene. The amount of C2 related carbons was quantified using all the mentioned signals according to the following equation: fC C2全 =(Iddg-ItwoB4)+(IstarB1×6)+(IstarB2×7)+(ItwoB4×9)+(IthreeB5×10)+((IstarB4plus-ItwoB4-IthreeB5)×7)+(I3s×3)
[0045] The amount of PP-related carbon was quantified using the integral of Sαα at 46.6 ppm, when characteristic signals corresponding to the presence of polypropylene (PP, continuous C3) were observed at 46.7 ppm, 29.0 ppm, and 22.0 ppm. fC PP =Isαα×3 The weight percent of the C2 fraction and polypropylene can be quantified according to the following formulas: wt C2画分 =fC C2全 ×100 / (fC C2全 +fC PP ) wt PP =fC PP ×100 / (fC C2全 +fC PP ) Characteristic signals corresponding to various short chain branches were observed and their weight percentages were quantified, beginning with quantifying the weight fraction of each, since the relevant branches are alpha olefins. fwtC2=fC C2全 -(IstarB1×3) -(IstarB2×4) -(ItwoB4×6) -(IthreeB5×7) fwtC3(isolated C3)=IstarB1×3 fwtC4=IstarB2×4 fwtC6=ItwoB4×6 fwtC7=IthreeB5×7 Normalization of all weight fractions results in weight percent amounts of all relevant branches. fsum 重量%全= fwtC2+fwtC3+fwtC4+fwtC6+fwtC7+fC PP wtC2 total = fwtC2 x 100 / fsum 重量%全 wtC3 total = fwtC3×100 / fsum 重量%全 wtC4 total = fwtC4 x 100 / fsum 重量%全 wtC6 total = fwtC6×100 / fsum 重量%全 wtC7 total = fwtC7 x 100 / fsum 重量%全
[0046] zhou07 Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D., Winniford, B., J.Mag.Reson. 187(2007) 225 busico07 Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128 singh09 Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5(2009), 475 randall89 J.Randall, Macromol.Sci., Rev.Macromol.Chem.Phys. 1989, C29, 201. brandolini00 AJBrandolini, DDHills, NMR Spectra of Polymers and Polymer Additives, Marcel Dekker Inc., 2000
[0047] d) Polymer composition analysis by CFC - Determination of homopolymer fraction (HPF), copolymer fraction (CPF) and iso-PP fraction (IPPF) The chemical composition distribution, as well as the molecular weight distribution at a specific elution temperature and the corresponding molecular weight averages (Mn, Mw and Mv) (polymer crystallinity in solution) were determined by fully automated cross-fractionation chromatography (CFC) as described by Ortin A., Monrabal B., Sancho-Tello J., Macromol. Symp., 2007, 257, 13-28.
[0048] Cross-fractionation chromatography (TREF×SEC) was performed using a CFC apparatus (PolymerChar, Valencia, Spain). Concentration was monitored using a 4-band IR5 infrared detector (PolymerChar, Valencia, Spain). The polymer was dissolved at a concentration of approximately 0.4 mg / ml at 160 °C for 180 min.
[0049] Weighed samples were packed into a stainless steel mesh MW 0.077 / D 0.05 mm to avoid injection of possible gels and polymers that are not soluble in TCB at 160° C., such as PET and PA.
[0050] Once the sample was completely dissolved, 0.5 ml aliquots were loaded onto the TREF column and stabilized at 110° C. for 60 min. The polymer was crystallized and precipitated by applying a constant cooling rate of 0.07° C. / min up to a temperature of 60° C. A discontinuous elution process was performed using the following temperature steps: (60, 65, 69, 73, 76, 79, 80, 82, 85, 87, 89, 90, 91, 92, 93, 94, 95, 95, 96, 97, 98, 99, 100, 102, 104, 107, 120, 130).
[0051] For the second dimension, GPC analysis, three PL Olexis columns and one Olexis Guard column from Agilent (Church Stretton, UK) were used as stationary phase. 1,2,4-Trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-ditert butyl-4-methyl-phenol) was applied as eluent at a constant flow rate of 1 mL / min at 150 °C. The column set was calibrated using universal calibration (according to ISO16014-2:2003) with at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The following Mark Houwink constants were used to convert PS molecular weights to PE molecular weight equivalents: K PS =19×10 -3 mL / g, α PS =0.655 K PE =39×10 -3 mL / g, α PP =0.725
[0052] Calibration data was fitted using third order polynomial fitting. Data processing was performed using software provided by PolymerChar in conjunction with the CFC instrument.
[0053] Calculation of homopolymer fraction (HPF), copolymer fraction (CPF) and iso-PP fraction (IPPF) The homopolymer fraction (HPF), copolymer fraction (CPF) and iso-PP fraction (IPPF) are defined as follows: 100%=CPF+HPF+IPPF For the above formula, the IPPF fraction is defined as the polymer fraction that elutes at a temperature of 104° C. or greater.
[0054] Due to the slight dependence of the T profile on the low MW fraction, the molecular weight limit of the low MW limit is determined by the elution temperature (T el The low MW limit was determined using the following formula: Low MW limit (for HPF fraction) = 0.0125 x T el +2.875 Taking this into account, the HPF fraction is calculated using the following approach.
number
[0055] e) Inorganic residue The ash content was determined by TGA according to DIN ISO11358-1:2014 using a TGA Discovery TGA5500. Approximately 10-30 mg of material was placed in a platinum pan. The samples were heated under nitrogen at a heating rate of 20 °C / min. The ash content was evaluated as wt% at 850 °C. f) OCS gel Cast film samples of approximately 70 μm thickness were extruded and inspected using a CCD (charge-coupled device) camera, an image processor and evaluation software (instrument: OCS-FSA100, supplied by OCS GmbH (Optical Control System)). Film defects were measured and classified according to their circular diameter. 2 of film was analyzed and the value per square meter was calculated as an average. Preparation of cast films, extrusion parameters 1. Output 25±4g / min 2. Extruder temperature profile: 200-210-210-200 (melt temperature 224℃) 3. Film thickness: approx. 70μm 4. Chill roll temperature: 80℃ 5. Air knife 6400NI / h (volume) Extruder Technical Data 1. Screw type: 3 zone, nitriding 2. Screw diameter: 25mm 3. Screw length: 25D 4. Feeding zone: 10D 5. Compression zone: 4D + output zone 11D 6. Die 150mm The defect size is (μm) / m 2 were classified according to the following. 100~299μm 300~599μm 600~999μm 1000μm or more
[0056] g) CIELAB color space (L * a * b * ) CIE L measured according to DIN EN ISO11664-4 * a * b * In the uniform color space, the color coordinates are: * -Brightness coordinate; a * - red / green coordinates, +a * indicates red, -a * indicates green;b * -yellow / blue coordinates, +b * indicates yellow, -b * indicates blue. * , a * , and b * The coordinate axes define the three-dimensional CIE color space. Standard Konica Minolta Colorimeter CM-3700A.
[0057] h) Evaluation of recycled properties ha) Limonene content Quantification of limonene can be performed using solid phase microextraction with standard addition (HS-SPME-GC-MS). 50 mg of ground sample is weighed into 20 mL headspace vials, different concentrations of limonene and a glass-coated magnetic stir bar are added, and the vials are closed with a silicone / PTFE-lined magnetic cap. Dilute limonene standards of known concentrations are added to the samples using a microcapillary (10 pL). Additions of 0 ng, 2 ng, 20 ng and 100 ng are equivalent to 0 mg / kg, 0.1 mg / kg, 1 mg / kg and 5 mg / kg of limonene, plus standard amounts of 6.6 mg / kg, 11 mg / kg and 16.5 mg / kg of limonene are used in combination with some of the samples tested in this application. Quantification is performed using ions 93 obtained in SIM mode. Concentration of the volatile fraction is performed by headspace solid-phase microextraction using a 2 cm Stable Flex 50 / 30 pm DVB / Carboxen / PDMS fiber at 60 °C for 20 min. Desorption is carried out at 270° C. directly in the heated injection port of the GCMS system. GCMS parameters: Column: 30m HP 5 MS 0.25 x 0.25 Injector: splitless, 0.75mm SPME liner, 270℃ Temperature program: -10℃ (1 min) Carrier gas: Helium 5.0, 31 cm / sec linear velocity, constant flow rate MS: Single quadrupole, direct interface, 280°C interface temperature Acquisition: SIM scan mode Scan parameters: 20~300amu SIM parameters: m / Z 93, dwell time 100 ms
[0058] hb) fatty acid detection Fatty acids are quantified using headspace solid-phase microextraction with standard addition (HS-SPME-GC-MS). 50 mg of ground sample is weighed into a 20 mL headspace vial and different concentrations of limonene and a glass-coated magnetic stir bar are added before closing the vial with a silicone / PTFE-lined magnetic cap. Using a 10 μL microcapillary, diluted free fatty acid mixture (acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, and optionally octanoic acid) standards of known concentration are added to the sample at three different levels. Additions of 0 ng, 50 ng, 100 ng and 500 ng are equivalent to 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg of each individual acid. For quantification, ion 60 obtained in SIM mode is used for all acids except propanoic acid, in which case ion 74 is used. GCMS parameters: Column: 20m ZB Wax plus 0.25×0.25 Injector: Glass-lined split liner, split 5:1 at 250°C Temperature program: 40°C (1 min), 6°C / min to 120°C, 15°C to 245°C (5 min) Carrier: Helium 5.0, 40cm / sec linear velocity, constant flow rate MS: Single quadrupole, direct interface, 220°C interface temperature Acquisition: SIM scan mode Scan parameters: 46~250amu 6.6 scans / sec SIM parameters: m / z 60, 74, 6.6 scans / sec
[0059] hc) metal It was determined by x-ray fluorescence (XRF).
[0060] hd) Benzene content According to the following HS GC-MS 80℃ / 2h.
[0061] Static Headspace Analysis The static headspace gas chromatography mass spectrometry (HS / GC / MS) method parameters applied are described here. 4.000±0.100 g of sample was weighed into a 20 ml HS vial and sealed with a PTFE cap. The mass spectrometer was operated in scan mode and total ion chromatograms (TIC) were recorded for each analysis. More detailed information on applicable method parameters and data evaluation is provided below.
[0062] HS parameters (Agilent G1888 headspace sampler) Vial equilibration time: 120 minutes Oven temperature: 80℃ Loop temperature: 205℃ Transfer line temperature: 210℃ low shaking GC parameters (Agilent 7890A GC system) Column: ZB-WAX 7HG-G007-22 (30m x 250μm x 1μm) Carrier gas: Helium 5.0 Flow rate: 2ml / min Split: 5:1 GC oven program: 35°C, 0.1 min. 10°C / min up to 250°C 250℃ 1 minute MS parameters (Agilent 5975C inert XL MSD) Acquisition mode: Scan Scan parameters: Low mass: 20 High mass:200 Threshold: 10 Software / Data Evaluation MSD ChemStation E.02.02.1431 MassHunter GC / MS Acquisition B.07.05.2479 AMDIS GC / MS Analysis Version 2.71 NIST Mass Spectral Library Version 2.0g AMDIS deconvolution parameters Minimum match factor: 80 Threshold: Low Scan direction: High to Low Data file format: Agilent files Instrument type: Quadrupole Component width: 20 Adjacent peak subtraction: Two Resolution: High Sensitivity: Very high Shape requirements: Medium Solvent tailing: 44 m / z Column bleed: 207 m / z Min.model peaks: 2 Min.S / N: 10 Min.certain peaks: 0.5
[0063] Data Evaluation The TIC data were further deconvoluted using AMDIS software (see parameters above) and compared to a custom targeted library based on the mass spectral library (NIST). This custom targeted library contained mass spectra of each of the selected substances (e.g., benzene). Substances were accepted as "tentatively identified" only if the recognized peaks showed a minimum match factor of 80 and the match was confirmed by an experienced mass spectrometer. In this study, the description "below the detection limit (<LOD)" refers to the condition that either the match factor is less than 80 (AMDIS) or the peak itself is not even recognized. The results refer only to the measured sample, the measurement time, and the applied parameters.
[0064] i) Odor VDA270 - B3 VDA270 is for the determination of the odor characteristics of trim materials in automobiles. The odor is determined according to the variant B3 of VDA270 (2018). The odor of each sample is evaluated by each assessor according to the VDA270 scale after lifting the lid of the bottle as low as possible. The six - step scale consists of the following grades: Grade 1: Imperceptible, Grade 2: Perceptible but not unpleasant, Grade 3: Clearly perceptible but not unpleasant, Grade 4: Unpleasant, Grade 5: Strongly unpleasant, Grade 6: Unacceptable. The assessors remain quiet during the evaluation and are not allowed to bias each other by discussing individual results during the test. The assessors are also not allowed to adjust their evaluations after testing another sample. For statistical reasons (and as accepted by VDA270), the assessors are forced to use the entire process in the evaluation. Therefore, the odor grade is rounded to an integer based on the average of all individual evaluations.
[0065] j) Tensile modulus of elasticity and tensile fracture strain Measured according to ISO527 - 2 (cross - head speed = 1 mm / min; test speed 50 mm / min, 23 °C) using injection - molded test specimens (dog - bone shape, thickness 4 mm) described in EN ISO17855 - 2. The measurement was carried out after a conditioning time of 96 hours (h) for the test specimens.
[0066] k) Impact strength Determined as the notched Charpy impact strength (1eA) (non - instrumented) in accordance with ISO179 - 1eA at +23 °C and - 20 °C for injection - molded test specimens of 80×10×4 mm prepared according to EN ISO1873 - 2.
[0067] l) Rheological parameters Dynamic Shear Measurements Dynamic shear characterization of polymer melts follows ISO standards 6721-1 and 6721-10. Measurements were performed on an Anton Paar MCR501 stress-controlled rotational rheometer with a 25 mm parallel plate geometry. Measurements were performed on compression molded plates using a nitrogen atmosphere and with strain set within the linear viscoelastic region. Oscillatory shear tests were performed at 190 °C applying a frequency range of 0.01-600 rad / s and with a gap set at 1.3 mm.
[0068] In dynamic shear experiments, the probe is subjected to uniform deformation with a sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In controlled strain experiments, the probe is subjected to a sinusoidal strain that can be expressed as: γ(t)=γ0sin(ωt) (1) If the applied strain is within the linear viscoelastic region, the resulting sinusoidal stress response can be given by: σ(t)=σ0sin(ωt+δ) (2) In the above formula, σ0 and γ0 are the stress and strain amplitudes, respectively. ω is the angular frequency, δ is the phase difference (loss angle between the applied strain and the stress response), where t is time.
[0069] Dynamic test results are typically expressed in terms of several different rheological functions: the shear storage modulus G', the shear loss modulus G", the complex shear modulus G * , complex shear viscosity η * , the dynamic shear viscosity η', the heterophase component of the complex shear viscosity η", and the loss tangent tan δ, and the rheological function can be expressed as follows:
[0070]
number
[0071] η(x kPa) is determined according to Equation 9. η(x kPa)=(G * = x kPa) * [Pa.s] (9)
[0072] For example, η(2.7 kPa) is defined by the value of the complex viscosity determined for a value of the complex modulus equal to 2.7 kPa. η(x rad / s) is determined according to Equation 10. η(x rad / s)=η for (ω=x rad / s) * [Pa.s] (10) For example, η(300 rad / s) is defined by the value of the complex viscosity determined in a frequency sweep of 300 rad / s.
[0073] Shear Thinning Factor (STF) and Polydispersity Index (PI) The shear thinning factor (STF) is defined as follows:
number
number
[0074] The value is determined by a single-point interpolation procedure defined by the Rheoplus software. * In situations where the values are not reached experimentally, the values are determined by extrapolation, using the same procedure as before. In both cases (interpolation or extrapolation), the option "- Interpolate y-values to x-values from parameter" and "logarithmic interpolation type" from Rheoplus was applied.
[0075] References: [1] “Rheological characterization of polyethylene fractions”, Heino, E. L., Lehtinen, A., Tanner, J., Seppala, J., Neste Oy, Porvoo, Finland, Theor. Appl. Rheol., Proc. Int. Congr. Rheol, 11th (1992), 1, 360-362 [2] "The influence of molecular structure on some rheological properties of polyethylene", Heino, E.L., Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995. [3]Definition of terms relating to the non-ultimate mechanical properties of polymers, Pure & Appl.Chem., Vol. 70, No. 3, pp. 701-754, 1998.
[0076] large amplitude oscillatory shear (LAOS) The study of nonlinear viscoelastic behavior under shear flow was carried out by means of large amplitude oscillatory shear. This method requires the application of a sinusoidal strain amplitude γ0 imposed at a given angular frequency ω for a given time t. If the applied sinusoidal strain is high enough, a nonlinear response is generated. In this case, the stress σ is a function of the applied strain amplitude, time and angular frequency. Under these conditions, the nonlinear stress response is still a periodic function. However, it can no longer be represented by a single harmonic sinusoid. The stress [0-0] resulting from the nonlinear viscoelastic response can be represented by a Fourier series including harmonic contributions. σ(t,ω,γ0)=γ0.Σn [G' n (ω,γ0).sin(nωt)+G” n (ω,γ0).cos(nωt)] (1) In the above formula, σ is the stress response, t is the time, ω is the frequency, γ0 is the strain amplitude, n is the harmonic number, G' n is the nth-order elastic Fourier coefficient, G” n is the nth-order viscous Fourier coefficient.
[0077] The nonlinear viscoelastic response was analyzed by applying large amplitude oscillatory shear (LAOS). Time sweep measurements were performed on an Alpha Technologies RPA2000 rheometer coupled with a standard biconical die. The test chamber is sealed and pressured at approximately 6 MPa during the course of the measurements. LAOS tests are performed at a temperature of 190°C, an angular frequency of 0.628 rad / s, and a strain of 1000%. To ensure that steady-state conditions are reached, the nonlinear response is determined only after at least 20 cycles per measurement are completed. The Large Amplitude Oscillatory Shear Non-Linear Factor (LAOS_NLF) is:
number
[0078] [1] J. M. Dealy, K. F. Issbrun, Melt Rheology and Its Role in Plastics Processing: Theory and Applications, edited by Van Nostrand Reinhold, New York (1990) [2] S. Filipe, Non-Linear Rheology of Polymer Melts, AIP Conference Proceedings 1152, pp. 168-174 (2009) [3] M. Wilhelm, Macromol. Mat. Eng. 287, 83-105 (2002) [4] S. Filipe, K. Hofstadler, K. Klimke, ATTran, Non-Linear Rheological Parameters for Characterization of Molecular Structural Properties in Polyolefins, Proceedings of Annual European Rheology Conference, 135(2010) [5] S. Filipe, K. Klimke, A.T.Tran, J. Reussner, Proceedings of Novel Non-Linear Rheological Parameters for Molecular Structural Characterisation of Polyolefins, Novel Trends in Rheology IV, Zlin, Czech Republic (2011) [6] K. Klimke, S. Filipe, ATTran, Non-linear rheological parameters for characterization of molecular structural properties in polyolefins, Proceedings of European Polymer Conference, Granada, Spain (2011)
[0079] Bottle manufacturing: 1 L bottles with an outer diameter of 90 mm, a wall thickness of 0.6 mm, an overall height of 204 mm and a cylindrical mantle height of 185 mm were produced by extrusion blow molding on a B&W machine equipped with a single screw extruder using a melt temperature of 190° C. and a die temperature of 15° C.
[0080] Bottle Drop Test (Progressive) During the progressive drop test, each bottle, as defined above, is dropped several times in rapid succession from increasing heights. The test is stopped for each bottle when failure occurs. The drop test is performed on 1 L bottles extrusion blow molded as described above. The bottles are filled with water up to the shoulder. For each test series, at least 12 bottles are required. Four bottles are dropped simultaneously from a starting height selected according to the table below. The expected breaking drop height has been determined in a pre-test or selected from experience.
[0081] [Table 1]
[0082] Bottles that show failure are discarded and the test continues with the remaining bottles, increasing in height. The size of the step of increasing height depends on the starting height. Below a starting height of 0.5 m, the step size is 0.1 m, whereas above 0.5 m the step size is 0.25 m. The failure drop height is recorded for each bottle and from the individual values the average failure drop height is calculated according to the following formula:
number
[0083] Working Example Several post-consumer plastic waste HDPE streams from a separate plastic waste collection (a civic amenity site providing a specific HDPE collection) were roughly screened with respect to polymer nature and color. Impurities were further separated by manual inspection. The two streams thus received, colorless (→IE1) and white fraction (→IE2), were (separately) subjected to grinding and washing in aqueous solutions containing various detergents, followed by drying and sieving to obtain the pretreated streams. The pretreated streams were further screened, which reduced the colored fraction and non-polyolefins. After extrusion into pellets, the substrate pellets were preheated to at least 100° C., after which the pellets were aerated with air at 120° C. for 22 hours. An essentially colorless example IE1 and a white example IE2 were obtained. For comparison purposes, a normal recycle CE1 (Purpolen) and a virgin bimodal polyethylene CE2 (in situ mixture of low molecular weight homopolymer and high molecular weight copolymer) were prepared and tested. The results of the final materials are shown in Table 1. For comparative purposes, virgin bimodal polyethylene CE2 (an in situ mixture of low molecular weight homopolymer and high molecular weight copolymer) was prepared by polymerizing ethylene and a very small amount of 1-butene.
[0084] All examples were subjected to polymer composition analysis by CFC.
[0085] [Table 2(1)] [Table 2(2)] [Table 2(3)] [Table 2(4)]
[0086] It can be seen that inventive examples IE1 and IE2 performed almost as well as the virgin material. Compared to the standard recycle blend, the inventive blend had significantly lower OCS gel counts. The notched Charpy impact properties were found to be better for inventive examples IE1 and IE2 when compared to virgin in situ bimodal blend CE2. The tensile yield stress was at a similar level for IE1 and IE2 compared to CE2. IE1 and IE2 also had good LAOS-NLF, shear thinning coefficient and polydispersity indicating excellent processability. IE1 and IE2 could be made into bottles, where these bottles had excellent quality (wall evenness, weld line and outer surface smoothness). The processability of IE1 and IE2 was even found to be the best among all the evaluated materials. Bottles made from IE1 and IE2 performed even better than CE2 in the drop test. In other words, 1:1 substitution of virgin bimodal polyethylene becomes possible for many applications, with further surprising advantages being observed with respect to bottle impact, processability and drop test stability.
Claims
1. A polyethylene blend comprising: (i) a melt flow rate of 0.1 to 10 g / 10 min (ISO 1133, 5.0 kg; 190° C.); and (ii) 950-970kg / m 3 density (ISO 1183), and (iii) a C2 fraction in an amount greater than 95.0% by weight of the d2-tetrachloroethylene solubles as determined by NMR; and (iv) a homopolymer fraction (HPF) content, determined according to chemical composition analysis by cross fractionation chromatography (CFC), in the range of 80.0 to 91.0 wt. %, and (v) a copolymer fraction (CPF) content, determined according to chemical composition analysis by cross fractionation chromatography (CFC), ranging from 9.0 to 20.0 wt. %, and (vi) optionally an iso-PP fraction (IPPF) content determined according to a chemical composition analysis by cross-fractionation chromatography (CFC) in the range of 0-2.0 wt.%, wherein the iso-PP fraction (IPPF) is defined as the polymer fraction eluting at a temperature equal to or greater than 104° C., and the homopolymer fraction (HPF), the copolymer fraction (CPF), and the iso-PP fraction (IPPF) together equal 100 wt.%; and (vii) 0.01 to 2.00 wt. % inorganic residue (as measured by TGA) based on the total polyethylene blend; and (viii) A 10 m OCS counting device in the range of 500 to 5,000 counts / m2. 2 OCS gels with sizes between 100 and 299 micrometers measured on films having (ix) the polyethylene blend comprises L 75.0-86.0 * , -5.0 to 0.0 a * , b 5.0 to less than 25.0 * , measured according to DIN EN ISO 11664-4 in the CIELAB color space (L * a * b * ) or or (x) the polyethylene blend comprises L over 86.0 to 97.0 * , -5.0 to 0.0 a * , b of 0.0 to less than 5.0 * , measured according to DIN EN ISO 11664-4 in the CIELAB color space (L * a * b * ) The polyethylene blend is a recycled material.
2. below a) limonene, determined using solid phase microextraction (HS-SPME-GC-MS), in amounts between 0.1 and 25 ppm; and b) The total amount of fatty acids from the group acetic acid, butanoic acid, pentanoic acid and hexanoic acid, determined using solid phase microextraction (HS-SPME-GC-MS), from 10 to 500 ppm.
2. The polyethylene blend of claim 1, comprising one or more of:
3. 2. The polyethylene blend of claim 1 having an odor (VDA270-B3) of 2.5 or less.
4. The following (10m 2 and having one or more of the following OCS gel count characteristics (measured on a film of a) OCS gels of size 300-599 micrometers: 100-2500 counts / m2; b) OCS gels of size 600-1000 micrometers: 10-200 counts / m2; c) OCS gels over 1000 micrometers in size: 1-40 counts / m2; All measurements were taken at 10m using an OCS counting device. 2 The measurements were taken on a film of 2. The polyethylene blend of claim 1.
5. 2. The polyethylene blend of claim 1 having a tensile modulus using injection moulded specimens as described in EN ISO 1873-2 (dog-bone shape, 4 mm thickness) (ISO 527-2 at a crosshead speed of 1 mm / min; 23°C) of at least 825 MPa.
6. quantitative 13 2. The polyethylene blend of claim 1, which has no units derived from isotactic polypropylene when subjected to C{H} NMR analysis.
7. Large Amplitude Oscillatory Shear-Nonlinear Factor (LAOS-NLF) (190°C; 1000%) [0010] is in the range of 2.1 to 2.9, G 1 ' is the first order Fourier coefficient, G 3 ' is the third order Fourier coefficient 2. The polyethylene blend of claim 1.
8. Shear Thinning Factor (STF) [0025] 2. The polyethylene blend of claim 1, wherein Mn is greater than 46.
0.
9. Polydispersity index (PI) [0030] is greater than 2.0, In the above formula, Gc is the crossover modulus, which is the value of the shear storage modulus G' when G' is equal to the shear loss modulus G".
2. The polyethylene blend of claim 1.
10. 10. The polyethylene blend of claim 1 in the form of pellets.
11. 13. An article made from the polyethylene blend of claim 1, wherein the polyethylene blend of claim 1 comprises at least 95% by weight of the reactants for making said article.
12. 13. An article made from the polyethylene blend of claim 1, wherein the polyethylene blend of claim 1 comprises at least 95% by weight of the reactants for making said article, said article being a bottle.
13. 10. A blend comprising the polyethylene blend of claim 1 and at least one virgin and / or recycled polyolefin.
14. 10. A method of providing the polyethylene blend of claim 1 for packaging.
Citation Information
Patent Citations
Recycling of high-density polyethylene from domestic polymer waste
EP2697025B1
Recycled resin composition
JP2020090656A
Process for removing volatiles from post-consumer recycled polyolefin chips
US5767230A
Method for producing polyolefin recyclates
WO2018046578A1